Hungarian Monitoring, 4 January 1988 . [Magyar rádiófigyelő], 1988. január 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Czechoslovakia: 'Rude Pravo' on 1968 - Polish inflation Domestic Affairs: - Governmental appointments and dismissals - Changes in the rules for passport applications Economy: - The tax and VAT systems - Changes in the prices of consumer goods - Industry: Ikarusz, Videoton, Duna Ironworks, Tatabánya mines Külpolitika: - Csehszlovákia: a Rude Pravo 1968-ról - Lengyel infláció Belpolitika: - Kinevezések és leváltások a kormányban - Változások az útlevélkérelemben Gazdaság: - Adó és ÁFA-rendszer - Fogyasztási cikkek árváltozása - Ipar: Ikarusz, Videoton, Dunai Vasmű, Tatabányai bányák